SPEECH ETIQUETTE AND CONCEPT “GRATITUDE” IN RUSSIAN, UZBEK AND ENGLISH LANGUAGES - Rukhsora Odilova; Shoira Yusupova (American Journals Publishing, 2023)
The article discusses the concept of speech etiquette, gives an interpretation of the concept of “gratitude”, describes the language means of expressing gratitude by native speakers of Russian, Uzbek and English.
Keywords: speech etiquette, concept, gratitude, language means, etiquette formulas, speech behavior, stereotypical formulas.